PERFORMANCE EVALUATION OF HYBRID SOLAR AIRWATER HEATER WITH VARIOUS INLET AIR TEMPERATURE DURING HEATING PROCESS - Hwi- Ung, Choi; Jung-In, Yoon; Chang-Hyo, Son; Kwang-Hwan, Choi (MATTER: International Journal of Science and Technology, 2015)
Research about hybrid solar air-water heater that can heating both air and liquid has been conducted for enhancing the usage of solar thermal energy. In the previous study, thermal efficiency of this collector was investigated with many operating and external conditions, but all of previous experiment conducted using outdoor air as inlet air of collector. Thus, in this study, the performance change of hybrid solar air-water heater was investigated with change of inlet air temperature during air and liquid were heated simultaneously. As a result, thermal efficiency for liquid heating was increased with increment of the inlet air temperature. On the contrary to this, thermal efficiency for air heating of collector was decreased with increment of inlet air temperature. In case of total thermal efficiency of collector considered air and liquid heat gain, it was also decreased with increment of inlet air temperature. From these results, it was confirmed that using outdoor air directly as inlet air of collector is better for the use of solar energy. However it is hard to conclude that which is better between using outdoor air and heated air on the perspective of energy saving of building because heat storage performance was increased if the return air or any heated air is used as inlet air of hybrid solar air-water heater when air and liquid was heated simultaneously even air and total thermal efficiency is decreased. Thus, the necessity of more profound study and consideration about this as a further study was also confirmed.